Complexation of metal ions with 3,5-di-tert-butyl-1,2-benzoquinone-1-monooxime, ESR studies of radical intermediates - Kasumov, VT; Tas, E; Kartal, I; Ucun, F; Köksal, F; Çukurovali, A (Gordon Breach Sci Publ Ltd, 2001)
The possibility of chelate formation of 3,5-di-tert-butyl-o-benzoquinone-1-monooxime with Cu(II), Co(II), Ni(II), Mn(II), Pd(II) metal ions under N-2 and in air have been investigated. It was found that complexation of metals except Cu(II) and Mn(II) was accompanied by formation of various stable radical species under air. The complexation of Co(II) even under N-2 unlike other metal ions, results in the formation of very stable radical species, which are assigned to phenazinyl type radical. ESR examination of reduction of bis(3,5-di-tert-butyl-o-benzoquinone-1-monooximato)M(II) (M = Cu, Pd,) with triarylphosphines P(C6H4X)(3) (X = H, m-Cl, m-CH3, p-Et2N) reveal the formation of the N-(2-hydroxy-3,5-di-tertbutylphenyl)-4', 6'-di-tertbutyl-o-benzosemiquinone iminate radical. Finally, ESR spectra of Cu(II), Ni(II), and Mn(II) complexes at 300 and 130 K, as well as reaction of bis(oximato)Ni(II) with PPh3 have been studied.
Keywords: 3,5-di-tert-butyl-1,2-benzoquinone-1-monooxime; optical and ESR spectra; radical intermediates; transition metal complexes